1994
DOI: 10.1128/mcb.14.6.4108-4115.1994
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Function of the Ras-Related Protein TC21/R-Ras2 Triggers Malignant Transformation

Abstract: Although the human Ras proteins are members of a large superfamily of Ras-related proteins, to date, only the proteins encoded by the three mammalian ras genes have been found to possess oncogenic potential. Among the known Ras-related proteins, TC21/R-Ras2 exhibits the most significant amino acid identity (55%) to Ras proteins. We have generated mutant forms of TC21 that possess amino acid substitutions analogous to those that activate Ras oncogenic potential [designated TC21(22V) and TC21(71L)] and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The Q72L, G23V and Dup24-26 RRAS2 mutations, analogous to the Q61L, G12V and Dup13-15 mutations in RAS proteins [ 22 ], can activate the transforming function of R-RAS2 in cell culture [ 2 , 11 , 32 , 33 ]. We have also recently shown that the Rras2 Q72L mutation acts as a potent oncogenic driver when somatically expressed in mice [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Q72L, G23V and Dup24-26 RRAS2 mutations, analogous to the Q61L, G12V and Dup13-15 mutations in RAS proteins [ 22 ], can activate the transforming function of R-RAS2 in cell culture [ 2 , 11 , 32 , 33 ]. We have also recently shown that the Rras2 Q72L mutation acts as a potent oncogenic driver when somatically expressed in mice [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…R-RAS2 (originally known as teratocarcinoma clone 21 or TC21) received significant attention upon its discovery in 1990 [ 1 , 2 ] since it was considered a potential surrogate oncogenic pathway for cancer cells lacking gain-of-function mutations in the classical RAS GTPases (H-RAS, K-RAS, N-RAS; referred to hereafter as RAS proteins). This idea was based on several features of R-RAS2 that were unique among the rest of RAS superfamily members: (i) 100% homology at the protein level of the two effector regions (switch I and switch II) with those present in RAS proteins [ 1 ]; (ii) binding to a similar spectrum of RAS regulators and proximal effectors such as PI3K, the RAL GDP dissociation stimulator (RAL GDS), and RAF family members [ 3 10 ]; (iii) similar subcellular localization as RAS proteins [ 3 5 ]; and (iv) transforming activity of some of gain-of-function R-RAS2 mutant versions similar to (or even higher than) RAS oncoproteins [ 2 , 11 ]. Despite these data, the interest in this GTPase faded away subsequently due to the inability to find gain-of-function RRAS2 mutations in human tumors with the techniques available before the emergence of next-generation sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to cisplatin, carboplatin, and EGFR-TKIs is inevitable in treating NSCLCs [7]. In lung cancer deregulation of TC21 can trigger cellular transformation and contribute to human oncogenesis because similar signal transduction pathway is used by oncogenic Ras [8]. Recent studies show that Rabl3 is a novel oncogene which regulates the oncological behaviour of human cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…RAS-related proteins (R-RAS) share several domains and regulatory factors with classical RAS proteins, mediating their activation and inactivation cycles, including guanine exchange factors (GEF) and GTPase activating proteins (GAP) [26]. Mutation of R-RAS2 in analogous residues to G12V and Q61L in classical RAS proteins has induced comparable cell transformation in culture and tumor growth in mice [27,28]. A key distinction is the high intrinsic nucleotide exchange activity of R-RAS2, allowing it to exchange GDP for GTP independently of specific GEF proteins at rates similar to those observed with H-RAS after GEF addition [29].…”
Section: Introductionmentioning
confidence: 99%